PENGARUH CUSTOMER EXPERIENCE DAN KEPUASAN TERHADAP PURCHASE INTENTION TIKTOK SHOP - Aghivirwiati, Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023, 2023)
The millennial generation currently has the convenience of accessing various kinds of applications, one of which is TikTok. TikTok provides online or online shopping features that allow anyone to make money through the features provided, namely the TikTok Shop, an online shopping feature offered by the TikTok platform. The purpose of this study is to find out and explain the influence of customer experience and satisfaction on purchase intention at the Tiktok Shop, and to know and explain the role of satisfaction in mediating the influence of customer experience on purchase intention at the Tiktok Shop. This research was conducted on tiktok users in Indonesia. The number of samples used in this study were 160 people. The analysis technique used is SEM-PLS. The results of this study indicate that customer experience and satisfaction affect purchase intention, and satisfaction is able to mediate the influence of customer experience on purchase intention.